PSIKOEDUKASI KARTU KUARTET UNTUK MENINGKATKAN AWARNESS SISWA SMP MENGENAI BAHAYA PENGGUNAAN NAPZA JENIS SABU DAN GANJA DI WILAYAH SAMARINDA KOTA - Rahayu, Hanis Kusumawati; Bakhtiar, Rahmat; Ramadhany, Candra; Nisa R, Indhira Zakhiatun (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2025)
There is growing concern about substance abuse among adolescents. Adverse effects on the central nervous system (brain), physical and psychological disorders, behavioral changes and other health problems. The method of intervention was carried out on 60 students in one of the public junior high schools in Samarinda City area. By using a pre-post test questionnaire, providing education through BNN and psychoeducation through quartet card game media. The results of the respondents were mostly female (56.8%). The majority of respondents were between 15 and 16 years old (86.7%). There was an increase in students' knowledge after receiving psychoeducation through quartet card games and reinforcement of material from BNN with p-value <0.001. Psychoeducation using game methods (quartet card media) and delivered by peers (peer educators) can improve the delivery of information and knowledge to the target population. In the future, peer educator training activities can be carried out at different locations of educational institutions in other regions